Epidemiological and nosological aspects of Leishmania naiffi Lainson & Shaw, 1989. - Naiff, Roberto Daibes; Freitas, Rui Alves de; Naiff, Maricleide de Farias; Arias, Jorge Ramon; Barrett, Toby Vincent; Momen, Hooman; Grimaldi Júnior, Gabriel F. (Memórias do Instituto Oswaldo Cruz, 1991)
Leishmania naiffi was isolated from 10 out of 64 armadillos (Dasypus novemcinctus) examined in Amazonas, Pará and Rondônia States in the Brazilian Amazon Region. The isolates were obtained in culture from samples of liver (3), spleen (3), lymph nodes (2), skin (1) and blood (1) from the infected animals. Heavy infections with the same parasite were detected for the first time in Psychodopygus squamiventris, a common man-biting phlebotomine, in Amazonas and Pará. A new case of cutaneous leishmaniasis caused by L. naiffi is described from the Manaus area, making a total of three known cases of human infection by this parasite.
Keywords: Adult; Animals; Brasil; Case Report; Classification; Human; Incidence; Isolation And Purification; Leishmania; Male; Parasitology; Skin Leishmaniasis; Skin Test; Adult; Animal; Brasil; Humans; Incidence; Leishmania; Leishmaniasis, Cutaneous; Male; Skin Tests